Insulin resistance is associated with an unfavorable outcome among non-diabetic patients with isolated moderate-to-severe traumatic brain injury – A propensity score-matched study - Cao, Cheng; Wang, Huxu; Gao, Heng; Wu, Wei (Frontiers in Neurology, 2022)
Background: Hyperglycemia is an independent risk factor for poor prognosis in patients with TBI, and stress-induced impaired insulin function is the major factor of hyperglycemia in non-diabetic TBI patients. Several research suggested that IR is related to the poor prognosis of neurocritical ill patients, here we focused on the role of IR in non-diabetic patients after TBI. Methods: We performed a prospective observational study with the approval of the Ethics Committee of our institute. IR was assessment via the update Homeostasis Model Assessment of IR (HOMA2), a computer-calculated index by glucose and insulin level. HOMA2 ≥ 1.4 was considered as the threshold of IR according to previous studies. The glycemic variability (GV) indices were calculated by fingertip blood glucose concentration at an interval of 2 hours within 24 hours to explore the relationship between IR and GV. The outcome was the 6-month neurological outcome evaluated with the Glasgow outcome scale. Results: 85 patients with isolated moderate-to-severe TBI (admission GCS ≤ 12) were finally included in our study, 34 (40%) were diagnosed with IR with HOMA2 ≥ 1.4. After propensity score matching (PSM), 22 patients in IR group were matched to 34 patients in non-IR group. Patients with IR suffered increased systemic glycemic variation after isolated moderate-to-severe TBI. IR was a significant factor for the poor prognosis after TBI (OR = 3.25，95% CI 1.03 -10.31, P = 0.041). Conclusions: IR estimated by HOMA2 was associated with greater GV and an unfavorable outcome after isolated moderate-to-severe TBI. Ameliorating impaired insulin sensitivity may be a potential therapeutic strategy for the management of TBI patients.